A novel crosswind mitigation strategy for tall buildings using negative stiffness damped outrigger systems - Wang, Meng; Nagarajaiah, Satish; Sun, Fei‐Fei (Structural control and health monitoring, 2022)
Summary This study presents a new crosswind mitigation strategy by using negative stiffness damped outrigger (NSDO) system for tall buildings. Using the “assisting motion” feature of negative stiffness, NSDO amplifies the motion of viscous damper resulting in and significant improvement of energy dissipation for tall buildings. Systematical evaluation and comparison on crosswind performance are carried out for tall buildings using (a) conventional outrigger (CO), (b) conventional damped outrigger (CDO), and (c) NSDO. It is shown that the proposed NSDO is able to achieve a damping amplification factor larger than a unit, which would never be achieved by CDO in practical due to the actual deformation of perimeter columns. In this way, NSDO has the most satisfactory crosswind reduction effect, especially when perimeter column stiffness is insufficient. For example, replacing CDO with NSDO not only attenuates crosswind‐induced harmful drift and structural acceleration by 22% and 36%, respectively, but also further saves about 75% of the size of viscous dampers. In other words, NSDO adopts less outrigger damping coefficient but reduces more crosswind‐induced vibration.